2014
DOI: 10.1152/japplphysiol.00420.2013
|View full text |Cite
|
Sign up to set email alerts
|

Acute change of titin at mid-sarcomere remains despite 8 wk of plyometric training

Abstract: The purpose of this study was to investigate skeletal muscle changes induced by an acute bout of plyometric exercise (PlyEx) both before and after PlyEx training, to understand if titin is affected differently after PlyEx training. Healthy untrained individuals (N = 11) completed the 1stPlyEx (10 × 10 squat-jumps, 1-min rest). Thereafter, six subjects completed 8 wk of PlyEx, while five controls abstained from any jumping activity. Seven days after the last training session, all subjects completed the 2ndPlyEx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…This research has shown that an intense, acute bout of PE (10 × 10 VJs) increased plasma CK activity and DOMS at 24–72 h post-exercise for the FG and the SG. The changes in CK were consistent with those observed following plyometric exercises with values peaking at 24 h after the damaging exercise in the firm and sand conditions [ 17 , 30 , 31 ]. Perceived soreness (DOMS) was also increased above the baseline value following muscle-damaging exercise, with peak values occurring at 48 h for participants in the SG and at 24 h for the FG.…”
Section: Evidence Of Muscle Damagesupporting
confidence: 82%
“…This research has shown that an intense, acute bout of PE (10 × 10 VJs) increased plasma CK activity and DOMS at 24–72 h post-exercise for the FG and the SG. The changes in CK were consistent with those observed following plyometric exercises with values peaking at 24 h after the damaging exercise in the firm and sand conditions [ 17 , 30 , 31 ]. Perceived soreness (DOMS) was also increased above the baseline value following muscle-damaging exercise, with peak values occurring at 48 h for participants in the SG and at 24 h for the FG.…”
Section: Evidence Of Muscle Damagesupporting
confidence: 82%
“…Histological stainings of exercised fibers already indicated changes in the intrasarcomeric abundance of titin (Lieber et al, 1996 ). More recently, a study using immunogold staining demonstrated that a single eccentric exercise bout induces a dislocation of the COOH terminus of titin toward the A band and H zone of the sarcomere, indicating exercise-induced stretch or fragmentation of the titin filament (Macaluso et al, 2014 ).…”
Section: The Role Of Titin In Exercise-induced Remodeling Of Skeletalmentioning
confidence: 99%
“…Such pre-digestion of muscle proteins has previously been demonstrated in septic muscle and was related to the activity of the calpain family of proteases (Williams et al, 1999 ). It has been demonstrated that acute eccentric exercise altered the expression levels of Calpain-2, and not of the titin-associated Calpains 1 or 3 (Lehti et al, 2009 ), but it significantly increased the autolysis and subsequent activation of Calpain-3 (Macaluso et al, 2014 ). Recent advances revealed that calpain-3 activation is not mediated by stretch alone, but is facilitated by the Ca 2+ -binding protein calmodulin and requires elevated levels of resting [Ca 2+ ],which occur e.g., during eccentric exercise (Ermolova et al, 2015 ).…”
Section: The Role Of Titin In Exercise-induced Remodeling Of Skeletalmentioning
confidence: 99%
“…PT in the form of vertical countermovement jumps on a solid surface is frequently used in studies as a way of provoking exercise-induced muscle damage (EIMD) in the knee extensors [7][8][9]. The effects of EIMD begin approximately 6 h after exercise, peak at 24-72 h, and subside 4-7 days after exercise [10][11][12].…”
Section: Introductionmentioning
confidence: 99%